2020
DOI: 10.1093/toxres/tfaa045
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of Coenzyme Q10 and liquid paraffin oil in the management of acute aluminum phosphide poisoning

Abstract: Abstract Aluminum phosphide (AlP) poisoning had high morbidities and mortalities with absence of a standardized approach for the treatment. The present study investigated the efficiency of GIT decontamination methods and Coenzyme Q10(Co Q10) (Ubiquinone) in improving the outcome of acute AlP poisoning. A total of 90 patients were included and all patients received immediately supportive measures, then they distributed into three equal groups: In group I, gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 30 publications
2
8
2
Order By: Relevance
“…In terms of sociodemographic data, toxicological data, clinical characteristics, laboratory investigation results, and ECG findings, there were no significant changes between the saline and both the paraffin and coconut groups. These were comparable to previous research ( Farahani et al, 2016;Elgazzar et al, 2019;Darwish et al, 2020;Emam et al, 2020;Helal et al, 2022). These findings suggest that the sequentially numbered opaque sealed envelopes (SNOSE) approach was used to achieve optimal randomization in this research.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In terms of sociodemographic data, toxicological data, clinical characteristics, laboratory investigation results, and ECG findings, there were no significant changes between the saline and both the paraffin and coconut groups. These were comparable to previous research ( Farahani et al, 2016;Elgazzar et al, 2019;Darwish et al, 2020;Emam et al, 2020;Helal et al, 2022). These findings suggest that the sequentially numbered opaque sealed envelopes (SNOSE) approach was used to achieve optimal randomization in this research.…”
Section: Discussionsupporting
confidence: 90%
“…After 12-hour from lavage, ABG showed nonsignificant values between the three studied groups. That disagreed with Darwish et al, (Darwish et al, 2020) who found that patients receiving paraffin oil lavage had non-significantly higher pH and PaCO2 values than the patients receiving potassium permanganate lavage solution (1:10000) at three-time intervals. Bicarbonate levels were significantly higher after 16 and 24 hours after admission.…”
Section: Discussionmentioning
confidence: 70%
“…There was a significant decrease in mortality in the case group (61.3%) compared with the control group (94.3%), which demonstrated that ILE infusion helped improve the outcomes of the cases. This mortality rate was lower than in many previous studies [15,20,21].…”
Section: Discussioncontrasting
confidence: 60%
“…These measures consecutively restore mitochondrial functions and ATP production and improve the contractility of the heart. Furthermore, CoQ10 can aid in improving the multiorgan dysfunction caused by acute AlP poisoning [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…With absence of specific antidote for aluminum phosphide poisoning the treatment of the AlP poisoning only is supportive and symptomatic (6) .…”
Section: Introductionmentioning
confidence: 99%